Analisa Keputusan Pembelian Mie oleh Konsumen Muda di Kota Bogor - Rara Sekar Ayu; Bayu Krisnamurthi; Dwi Rachmina (Jurnal Agribisnis Indonesia, 2024)
The advancement of technology and society have led to changes including food choice patterns among citizens, especially the younger generation that prefers fast food. Noodles are included in one of the fast foods that young people opt for as it has diverse varieties. The decision-making process of purchasing noodles for young consumers is influenced by several driving factors. This study aims to analyze the decision-making process among young customers in Bogor while buying noodles, analyze factors that influence the decision-making while purchasing noodles in Bogor, and formulate managerial implications for the development of Noodles SMEs. Primary data from a survey of 95 respondents were analyzed using descriptive analysis and SEM-PLS analysis. The results indicate that consumers buy noodles primarily because they are fast and convenient while considering the taste of the product. Personal experience is the most influential factor in their purchasing decisions. There are four significant factors influencing the purchasing decisions of young consumers regarding wet noodles in Bogor, including product factors, distribution, promotion, and lifestyle. The distribution factor has the highest influence on consumer purchasing decisions with the highest correlation value. The efforts noodle SMEs in order to develop their businesses include maintaining and increasing the distribution of products as this factor is the most influential factor for customers to do the purchasing.